IMPLIKASI DUALISME KEPENGURUSAN DEWAN PIMPINAN PUSAT PARTAI GOLKAR TERHADAP PELAKSANAAN PEMILIHAN KEPALA DAERAH SERENTAK - Sinurat, Evita Everon; Indra, Mexsasai; ', Junaidi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Golkar Party is considered a fairly representative media to participate in defining policies through constitutional system. Now the existence of the Golkar Party is undergoing a political storm with the duality of its staff. This dispute affect the implementation of the local elections simultaneously held on December 9, 2015, which affects the cadres of the Golkar Party will go forward as a candidate for regional heads in unison for causing confusion are most valid its staff in determining a recommendation for applying to the Commission and also will affect public support to be not optimal. The purpose of writing this skrisi is; First, to determine the management of efforts to resolve the duality of the Golkar Party Central Executive Board. Second, to determine the implications of duality management Golkar Party Central Executive Board on the implementation of the local elections simultaneously.This type of research can be classified in this type of normative juridical research, ie research that discusses asa-legal principles, systematic law, the degree of synchronization of law, in this case the researchers discuss the principles of law. This research was conducted by examining the library materials or secondary data such as legislation and books written by lawyers associated with the title of the research, articles, journals and various other sources. Source data used are secondary data sources. Secondary data are divided into three types: primary legal materials, secondary law and tertiary legal materials, data collection techniques used in this research study method study literature or documentary.From the research problem there are two main things that can be inferred. First, in the end the internal conflict through the duality of the Golkar Party, administration of the results of these two different National Conference, resolved and determined by the court. Secondly, the implications of dualism management Golkar Party Central Executive Board have resulted in the absence of legal certainty in the management of the party and the resulting impact on the determination of candidates for regional heads who participated in local elections simultaneously on December 9, 2015. Since when has a different letter of recommendation, then registration will not be accepted by the Commission and also affect the support from the public becomes less than the maximum because the Golkar party disputes. Suggestions Author, First, the Golkar Party is expected to solve the problem of dualism via the mechanism of management of internal party beforehand, and when completed by an external party, in this case Menkumham must be neutral and keep political considerations in the management of the party's endorsement. Second, the expected political parties in completing the internal dynamics of the party, must still give priority to constituents and sought to position itself in accordance with the objectives of the political party, which political parties should be statesman who put the interests of the community / nation and put aside political interests.Keywords: Implications - Dualism - Golkar Party - Simultaneous elections